A cobrança de multas e indenizações decorrentes das hipóteses de litigância de má-fé previstas pelo artigo 17 do Código de Processo Civil - Muniz, Maristela Cury (2010)
The aim of this work is to establish a concept of malicious fraud and to systematize the ways of execution of penalties and condemnations of lawsuits for damages, both resulted from the hypothesis described by the article 17th of the Brazilian Civil Procedural Code. The justification of this work is that the lack clarity of the malicious fraud s legislation, its concept, importance and application is embarrassing the repression, by the Judge, of malicious fraud s manifestations, which are each time more commonly verified and aggravated. This circumstance, indirectly, stimulate the practice of malicious fraud and procedural chicanery, offending Justice s dignity. In this manner, this work will examine some aspects of the execution of penalties and condemnations of lawsuits for damages, both resulted from the hypothesis described by the article 17th of the Brazilian Civil Procedural Code, so that it will be demonstrated, here, how simple and practicable its application can be